Endobronchial ultrasound in diagnosing and staging of lung cancer by Acquire 22G TBNB versus regular 22G TBNA needles: A randomized clinical trial - Kramer, Tess; Kuijvenhoven, Jolanda C; von der Thüsen, Jan; Cohen, Daniëlle; Szlubowski, Artur; Gnass, Maciej; Ninaber, Maarten K; Hoppe, Bart; Trisolini, Rocco; Sestakova, Zuzana; Votruba, Jiri; Korevaar, Daniël A; et al. (Lung cancer (Amsterdam, Netherlands), 2023)
•The PD-L1 suitability rate between the 22G Acquire TBNB and Expect TBNA needle is similar.•Both needles have high sensitivities for diagnosing and staging lung cancer.•Acquire TBNB needle procures improved quality tissue specimens with more tissue cores. Endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) has an important role in the diagnosis and staging of lung cancer. Evaluation of programmed death ligand 1 (PD-L1) expression and molecular profiling has become standard of care but cytological samples frequently contain insufficient tumor cells. The 22G Acquire needle with Franseen needle tip was developed to perform transbronchial needle biopsy (TBNB) with improved tissue specimens. This study evaluated if the 22G Acquire TBNB needle results in enhanced PD-L1 suitability rate compared to the regular Expect 22G TBNA needle. in this multi-center randomized clinical trial (Netherlands Trial Register NL7701), patients with suspected (N)SCLC and an indication for mediastinal/hilar staging or lung tumor diagnosis were recruited in five university and general hospitals in the Netherlands, Poland, Italy and Czech Republic. Patients were randomized (1:1) between the two needles. Two blinded reference pathologists evaluated the samples. The primary outcome was PD-L1 suitability rate in patients with a final diagnosis of lung cancer. In case no malignancy was diagnosed, the reference standard was surgical verification or 6 month follow-up. 154 patients were randomized (n = 76 Acquire TBNB; n = 78 Expect TBNA) of which 92.9% (n = 143) had a final malignant diagnosis. Suitability for PD-L1 analysis was 80.0% (n = 56/70; 95 %CI 0.68–0.94) with the Acquire needle and 76.7% (n = 56/73; 95 %CI 0.65–0.85) with the Expect needle (p = 0.633). Acquire TBNB needle specimens provided more frequent superior quality (65.3% (95 %CI 0.57–0.73) vs 49.4% (95 %CI 0.41–0.57, p = 0.005) and contained more tissue cores (72.0% (95 %CI 0.60-0.81) vs 41.0% (95 %CI 0.31–0.54, p < 0.01). There were no statistically significant differences in tissue adequacy, suitability for molecular analysis and sensitivity for malignancy and N2/N3 disease. The 22G Acquire TBNB needle procured improved quality tissue specimens compared to the Expect TBNA needle but this did not result in an improved the suitability rate for PD-L1 analysis.